Проекційні методи розв’язання нелінійних варіаційних нерівностей - Panin, V. M.; Lavrina, T. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Finite-dimesional variational inequalities with a strongly monotone operator and numerical methods for their solution are considered. First order projectional methods with linearisation of constraints based on quadratical programming are studied. Nonlocal convergence to solution and geometrical convergence in its neighborhood are proved.